PENCAPAIAN KINERJA PETANI DENGAN PENDEKATAN BALANCED SCORECARD (STUDI KASUS KELOMPOK TANI KAKAO SIDODADI DESA PUTAT KECAMATAN PATUK KABUPATEN GUNUNG KIDUL) - Munawaroh, Shofiyatun; Harli, Nurlina (Agros Journal of Agriculture Science, 2024)
Gumawang Hamlet has its own managed cocoa farming, but the income it earns has not increased so it is important for farming to have an objective and transparent performance assessment system. The objective to be achieved in this research is to determine the performance results of the Sidodadi Farmer group farmers when measured using the Balanced Scorecard approach. The method used in this research is the Balance Scorecard approach. Key performance indicators are measured by comparing the level of achievement (realization) with the Budget Work Plan (RKAP) that has been determined for the same year. The performance measurement results using the 7 indicators in the questionnaire show that 4 factors have quite good scores. These 4 factors are as follows: 1) work wisely in land problems with an average of 3.5% weight value 27. 2) work diligently with an average of 3.2% weight value 15. 3) work neatly with an average value of 3.2% weight value 15. 4) farmers master knowledge with an average of 3.2% weight value 15.